The Implementation of Blendid Learning in Islamic Education Students - Nindya Juwita Utimadini (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2020)
Autonomous learning has been one of the issues that sparked other terms and being discussed in EFL field. It is believed that autonomous learning and reading comprehension is having a positive relationship. Many researchers also agree that autonomous readers have great ability to deal with difficult reading. Therefore, this article aimed to explore one of the most achieving students in English Language Educati on Department scheme in her reading activity. This article focuses on the four characteristics that needs to be gained by the learners to be autonomous; 1) Having capacity to make own decision concerning EFL reading; 2) Having capacity to control EFL reading 3) Having responsibility in EFL reading; 4) Having self efficacy in reading”. The research unfolds the fact that during the reading activity, the successful student has the four characteristics